2019
DOI: 10.7160/eriesj.2019.120202
|View full text |Cite
|
Sign up to set email alerts
|

Lesson Study for Professional Development of English Language Teachers: Key Takeaways from International Practices

Abstract: Even though various professional development practices are provided for language teachers worldwide, these practices are still considered ineffective in addressing teachers' needs in their classrooms. The effectiveness of these practices is stalled when teachers do not actively engage in their professional development processes. When language teachers are not involved as active decision makers regarding their own professional development practices, the outcomes may not be as desirable as policymakers plan. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…In 2019, a systematic review of lesson study implementations by English language teachers around the world and in Turkey was carried out by Uştuk and Çomoğlu (2019), who recommended the model to be adopted by more languages teachers. Karabuğa and İlin (2019) conducted a qualitative study with five EFL teachers and discussed the potential advantages and disadvantages of the model in depth.…”
Section: Lesson Study In Turkeymentioning
confidence: 99%
“…In 2019, a systematic review of lesson study implementations by English language teachers around the world and in Turkey was carried out by Uştuk and Çomoğlu (2019), who recommended the model to be adopted by more languages teachers. Karabuğa and İlin (2019) conducted a qualitative study with five EFL teachers and discussed the potential advantages and disadvantages of the model in depth.…”
Section: Lesson Study In Turkeymentioning
confidence: 99%
“…Having been accepted as a bottom-up approach (Saito et al , 2020; Uştuk and Çomoğlu, 2019), LS is seen as an alternative to the conventional forms of top-down PD. Reviewing earlier studies, Fujii (2016) conceptualizes several principles of LS practice that challenges the conventional approaches.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is also evident that teachers' PD has become one of the most central interests in educational research over the past several decades, and numerous studies conducted all over the world have shown that PD activities within and outside the educational setting influence teachers positively (e.g., Joshi et al, 2018;Krille, 2020;Mohammadi & Moradi, 2017;Özgehan & İrem, 2019). Through his review of the literature, Bayar (2014) stated that PD activities potentially help both novice and experienced teachers in enhancing their existing skills and obtaining new ones.…”
Section: List Of Figuresmentioning
confidence: 99%